Urbanization and child nutritional outcomes - Amare, Mulubrhan; Arndt, Channing; Abay, Kibrom A.; Benson, Todd (Oxford University Press, 2020)
In this paper, the relationship between urbanization and child nutritional outcomes is investigated using satellite-based nighttime light intensity data as a proxy for urbanization and urban growth. Geo-referenced and nationally representative data from two rounds (2008 and 2013) of the Demographic and Health Survey (DHS) from Nigeria is employed. The DHS data provide detailed anthropometric measures of child nutritional outcomes along with a series of control variables. These geo-referenced DHS data are merged with nighttime light intensity data for the survey clusters in which the DHS sample households reside. This nighttime light introduces a gradient of urbanization permitting investigation of the implications of urbanization on child nutritional outcomes along an urbanization continuum.